Using teleprimary care to monitor immunization status in Sarikei Health Clinic, Sarikei, Sarawak - Lai, B.F; Razitasham Safii,; Lebia Nyulan,; Christina Dunggau,; Mohd Asri Riffin,; Khu F.M.,; Ong, Flora, (Universiti Kebangsaan Malaysia, 2011)
The purpose of this paper is to demonstrate the effectiveness of using TelePrimary Care (TPC) to monitor immunization programmed in a clinic. Japanese Encephalitis (JE) vaccination was selected as an example because its coverage has not been satisfactory when compared to that of other vaccinations, which generally exceed 90%. Data for all children who were eligible for JE vaccination (age range from 9 months to 30 months) who attended Sarikei Health Clinic between 1 January 2007 till 31 June 2008, was extracted from the TPC database and analyzed for completeness and timeliness of JE vaccination. The analysis showed that although 1,243 children were eligible to receive their first dose of J vaccine at 9 months of age, only 560 (45%) received it. 15 (3%) received on time, and 545 (97%) received it late (age range from 10 months to 20 months). Out of the 560 who were scheduled to receive their second dose of JE vaccine four weeks after the first, 382 (88%) received it on time, and 55 (12%) received it late. Only 78 (18%) out of 429 children aged between 18 months to 24 months received their booster dose; 52 (67%) received it on time and 26 (33%) received it late.TPC not only enables health staff to monitor immunization coverage and timeliness accurately, but it also helps them to identify defaulters quickly so that these children can be traced and immunized. Doing these tasks manually is time-consuming and tedious, leading to delays in tracing defaulters. TPC provides an effective system for staff to easily access real time child health data to monitor and audit their immunization programme and take remedial action where necessary.